Atributos de substratos com rejeito de lavra de bauxita cultivados com Puerária (Pueraria phaseoloides) e Braquiaria (Brachiaria decumbens) em Barro Alto, Goiás - PAULA, érica Cristina Martins de (2010)
The attributes of a substratum composed by tailings from mining of bauxite, cultivated with Pueraria (Pueraria phaseoloides)and brachiaria were studied for the flora recomposition in Barro Alto, Goiás. In order to reach that aim, the phytotechnical performance was assessed through the stalk height and diameter for legume and height and number of basal tillers for grass, besides green and dry phytomass for both species. The chemical attributes were also evaluated, through chemical analyses of the substratum at the beginning and at the end of the experiment as well as the physical and microbiological attributes. The experiments were conducted in vases in the city of Barro Alto, GO, from dezember 2008 to june 2009. The delimitation used were random blocks, with four repetitions and composed by 17 treatments with diferent compositions of cattle manure (0% to 20,5%), sugar cane bagasse (0% to 40%) and clayey tailings (45% to 90%), and different doses of phosphorus for three living roofs (B. decumbens, P. phaseloides e B. decumbens + P. phaseoloides). The treatment, which the grass and legume had a better phytotechnical performance are those that present manure concentratios above 10%. Concerning the chemical attributes, initially the treatment with at least 3,5% of manure, and 8,5% of bagasse with no phosphorous (T5), showed chemical properties suitable for plant growth, although there was a low content for organic matter. The substratum that had better physical characteristics, were those with at least 17,5% of sugar cane bagasse, besides that, the simultaneously addition of bovine manure and sugar cane bagasse allowed better values regarding soil microbes.